Biochemical study of collagen formation in healing wounds under the effect of Serotonin (5-Hydroxytryptamine)* - R. N. Sinha; C. N. Malla (Indian Journal of Plastic Surgery)
The change in the concentration of a component of biochemical interest was studed over a period of 15 days under the effect of serotonin.